Correlation between interleukin-6 and septic shock in children - Stephanie Yulianto; Ari Runtunuwu; Vivekenanda Pateda; Jose Mandei; Julius Lolombulan (Paediatrica Indonesiana, 2012)
Background Sepsis is a lifeô€†threatening condition and the mostcommon cause of death in intensive care units in developingcountries, such as Indonesia. The first clinical signs of sepsis areusually nonô€†spedfic. More specific signs and laboratory parametersoften occur late and are associated 'With organ dysfunction andhigh mortality rates. Interleukinô€†6 (IL--6) is a biomarker reported tobe superior to clinical signs and conventional tests for sepsis. IL--6levels may indicate microorganism invasion, as well as progressionof infection into sepsis, severe sepsis, and septic shock.Objective To evaluate a correlation between interleukin (IL)ô€†6and septic shock in childrenMethods This crossô€†sectional study was conducted in the pediatricintensive care unit of Prof. Dr. R.D. Kandou Hospital, Manado,between June to September 2011. Subjects were children withsepsis or septic shock aged 1 month to 13 years, v.ith diagnosesbased on the International Pediatric Sepsis Consensus ConferenceCriteria 2005. A oneô€†time measurement of IL--6 plasma levelswas done at the time of diagnosis. Data was analyzed by logisticregression test using SPSS version 17 software. A P value of <0.05indicated statistical significance.Results The mean IL--6 plasma level in the septic group was 1.68(95%CI 1.45 to 1.91) pg/mL and that of the septic shock groupwas 2.33 (95%CI 1.79 to 2.86) pg/mL. Our results showed astrong positive correlation between ILô€†6 plasma levels v.ith theprobability of septic shock in children v.ith sepsis (regressioncoefficientô€‡1.3lO, Pô€‡O.024).Conclusion Higher plasma IL--6 levels were associated v.ith ahigher risk of septic shock in children with sepsis. [Paediatrrndones.2012;52:352-5].